Barriers and Facilitators to Self-Directed Learning in Continuing Professional Development for Physicians in Canada: A Scoping Review. (August 2018) - Jeong, Dahn; Presseau, Justin; ElChamaa, Rima; Naumann, Danielle N.; Mascaro, Colin; Luconi, Francesca; Smith, Karen M.; Kitto, Simon
Abstract : Purpose: This scoping review explored the barriers and facilitators that influence engagement in and implementation of self-directed learning (SDL) in continuing professional development (CPD) for physicians in Canada. Method: This review followed the six-stage scoping review framework of Arksey and O'Malley and of Daudt et al. In 2015, the authors searched eight online databases for English-language Canadian articles published January 2005–December 2015. To chart and analyze data from the 17 included studies, they employed a two-step analysis process composed of conventional content analysis followed by directed coding applying the Theoretical Domains Framework (TDF). Results: Conventional content analysis generated five categories of barriers and facilitators: individual, program, technological, environmental, and workplace/organizational. Directed coding guided by the TDF allowed analysis of barriers and facilitators to behavior change according to two key groups: physicians engaging in SDL, and SDL developers designing and implementing SDL programs. Of the 318 total barriers and facilitators coded, 290 (91.2%) were coded for physicians and 28 (8.8%) for SDL developers. The majority (209; 65.7%) were coded in four key TDF domains: environmental context and resources, social influences, beliefs about consequences, and behavioral regulation. Conclusions: This scoping review identified five categories of barriers and facilitators in the literature and four key TDF domains where most factors related to behavior change of physicians and SDL developers regarding SDL programs in CPD were coded. There was a significant gap in the literature about factors that may contribute to SDL developers' capacity to design and implement SDL programs in CPD. Abstract : Supplemental Digital Content is available in the text.